PELATIHAN INTEGRASI KECERDASAN BUATAN DALAM PENGEMBANGAN BAHAN AJAR INTERAKTIF UNTUK GURU DI SEKOLAH TUNAS JAKASAMPURNA - Afifah Arifuddin, Nurul; Dwi Amalia, Rifka; Setyadinsa, Radinal (Universitas Muhammadiyah Tapanuli Selatan, 2024)
The use of technology in education has seen rapid development over the past few decades, with Artificial Intelligence (AI) becoming one of the most prominent technologies. AI has the potential to enhance the effectiveness and efficiency of teaching and learning processes, particularly in the development of interactive teaching materials. The training titled